Penilaian Kinerja Keuangan Pemerintah Daerah Kabupaten Tulungagung Tahun 2021-2023 - Nada, Raicha Nabila; Mubarok, Ujang Syahrul; Akbar, Taufik (STIE AMKOP, 2025)
This study aims to evaluate the financial performance of the Regional Government of Tulungagung Regency during the 2021–2023 period using four financial ratios: regional financial independence ratio, the effectiveness ratio of locally-generated revenue (PAD), activity ratio, and growth ratio. Data were obtained from the Regional Budget Realization Report and analyzed using a descriptive quantitative method. The results show that Tulungagung Regency has performed well in terms of revenue, with actual income exceeding the budget target. However, expenditure realization remains below the allocated budget, indicating issues in planning and budget execution. The local government still heavily relies on central government transfers, thus financial independence has not been fully achieved. The findings of this research are expected to serve as a basis for evaluating and improving regional financial management. Keywords: Financial Performance, Local Government, Financial Ratio